Droplet-based Synthesis of Homogeneous Gold Nanoparticles for Enhancing HRP-based ELISA Signals - Choi, Ji Wook; Kim, Young Jae; Lee, Jong Min; Choi, Jin-Ha; Choi, Jeong-Woo; Chung, Bong Geun (Biochip journal, 2020)
Gold nanoparticles (AuNPs) have widely used for various biological applications, such as drug screening, photo-thermal therapy, and biosensing. In particular, the synthesis of AuNPs with narrow size distribution plays an important role in increasing the efficiency of nanoparticle-mediated biosensors. However, the conventional synthesis methods (e.g., citrate reduction method) still suffer from controlling the sizes of the nanoparticles. In this paper, we present the synthesis method of homogeneous AuNPs using a droplet-based microfluidic chip. Prior to experiments, we optimized the size of droplets using a simulation software for stable droplet generation. We demonstrated that the nanoparticles synthesized in our microfluidic chip system showed a narrower size distribution and a higher reproducibility compared to conventional batch synthesis. Furthermore, we observed that the signal of anti-horseradish peroxidase (HRP) was significantly enhanced by the droplet-based microfluidic chip. Therefore, our synthesis method of homogeneous AuNPs could play an important role in improving the efficiency of AuNPs-based sensing signals.